(untitled) (Raparin Journal of Humanities (RJH), 2025)
The results of a number of relevant studies and research indicated the need to pay attention to people with cerebral palsy in childhood and provide a rehabilitation program to improve motor skills on the one hand and skills for life and daily activities on the other hand. Rehabilitating motor abilities is one of the common problems among children with spastic cerebral palsy in general and those with diplegic cerebral palsy in particular.The researcher used the experimental method with a one-group experimental design with two pre- and post-tests to suit the nature of the research.The sample included to participate in the rehabilitation program consisted of (8) children with double spastic cerebral palsy, who were among those with second degree paralysis and who attended the Jawarbakh Rehabilitation Center in Sulaymaniyah Governorate. After reviewing specialized scientific books, previous research and studies, and personal interviews with experts and specialists in the field of rehabilitation for the disabled in general and cerebral palsy in particular, the researcher prepared and designed the proposed rehabilitation exercises for a period of three months, and the rehabilitation units (sessions) are three rehabilitation units per week.The results indicated significant differences between the two tests (pre-post) in the variables studied, and this means the progressive development of the program using qualifying exercises for the research sample.